Intersectionality: What does it mean and how can we better engage with it? - Ihalainen, Markus (Center for International Forestry Research, 2017)
Presented by Markus Ihalainen (CIFOR), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.